HUBUNGAN INDEKS KEBERSIHAN GIGI DAN MULUT DENGAN INDEKS KARIES GIGI PADA MURID SDN 03 PAKAN KURAI KECAMATAN GUGUK PANJANG KOTA BUKITTINGGI - Zulfikri Zulfikri; Zakya Ismatul Huda (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2017)
TITLEThe relation between oral hygiene index and dental caries index in students of SDN 03 Pakan Kurai, Guguk Panjang, BukittinggiABSTRACTOral hygiene is a risk factor for dental caries, so that the dental and oral hygiene are directly related to the occurrence of caries. The aim of research to determine the relationship of oral hygiene with dental caries index. The scope of the research includes dental and oral hygiene with dental caries index students.The research method descriptive analytic approach